STRUCTURAL PATTERNS IN ELT CONFERENCE PROCEEDING INTRODUCTIONS - Mahmud Yusron; Ima Fitriyah (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Research article introductions play an important role in establishing the significance, focus, and contribution of a study. Although many studies have examined the rhetorical structure of research article introductions, limited attention has been given to introductions in English language teaching conference proceedings, particularly those written by Indonesian student writers. This study aims to identify the generic structure of introduction sections in ten English language teaching conference proceeding articles written by students from English education study programs in Indonesia. Using a qualitative case study design, the study analysed the introductions based on the modified CARS (Create a Research Space) model. The findings show that Move 1, establishing a territory, and Move 3, occupying a niche, appeared in all introductions, whereas Move 2, establishing a niche, appeared less consistently. The most frequent steps were claiming centrality, making topic generalisations, counter-claiming, outlining the purpose, and listing research questions or hypotheses. However, reviewing previous research, indicating a gap, continuing a tradition, and stating the value of the research appeared less frequently. These findings suggest that the writers were generally able to introduce their topics and present their studies, but they need stronger rhetorical awareness in using previous literature to establish clear research gaps and justify the significance of their research.